2009
DOI: 10.1093/pcp/pcp159
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis NAC Transcription Factor, ANAC078, Regulates Flavonoid Biosynthesis under High-light

Abstract: We have isolated a combination of high-light and heat-shock (HL + HS) stress-inducible genes, including a NAC transcription factor designated ANAC078. Here we explored the physiological function of ANAC078 under HL stress. Yeast transcription activity assays showed that ANAC078 functions as a transcriptional activator. A fusion protein composed of green fluorescent protein (GFP) and full-length ANAC078 was detected in the nucleus and cytoplasm, while fusion proteins comprising GFP and ANAC078 deleted of a puta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
153
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(164 citation statements)
references
References 61 publications
7
153
1
3
Order By: Relevance
“…Previous functional studies indicated that ANAC078 regulates light stress-dependent flavonoid biosynthesis and proteasome levels (Morishita et al, 2009;Yabuta et al, 2011). In transgenic Arabidopsis plants overexpressing ANAC053, leaf senescence was promoted during drought stress (Lee et al, 2012).…”
Section: Anac013 Regulates Mrrmentioning
confidence: 98%
“…Previous functional studies indicated that ANAC078 regulates light stress-dependent flavonoid biosynthesis and proteasome levels (Morishita et al, 2009;Yabuta et al, 2011). In transgenic Arabidopsis plants overexpressing ANAC053, leaf senescence was promoted during drought stress (Lee et al, 2012).…”
Section: Anac013 Regulates Mrrmentioning
confidence: 98%
“…The transcription factors and transcription complexes can act as positive or negative regulators in flavonoid biosynthesis Yang et al 2017). Other transcription factors, apart from R2R3-MYBs and bHLHs, e.g., Basic Leucine Zipper Domain (bZIP) or NAC, have been reported as positive regulators of flavonoid biosynthesis (Morishita et al 2009;Malacarne et al 2016). The single repeat MYBs (R3-MYBs), squamosa promoter binding protein like (SPL), or some NAC TFs, have been reported as negative regulators of flavonoid biosynthesis in plants (Dubos et al 2008;Gou et al 2011;Dalman et al 2017).…”
Section: Regulation Of Flavonoid Biosynthesis In Plants: a Comparisonmentioning
confidence: 99%
“…GmNAC1, GmNAC5 and GmNAC6 transiently expressed in tobacco leaves, resulting in cell death and enhanced expression of senescence markers. Flavonoid biosynthesis is regulated by ANAC078 under high-light (Morishita et al, 2009). A rice NAC gene, ONAC045 was induced by drought, high salt, low temperature, and ABA treatment in leaves and roots (Zheng et al, 2009).…”
Section: The Nac (Nam Ataf and Cuc) And Zf-hd (Zinc-finger Homeodomamentioning
confidence: 99%